Learning developers as third space academics: a personal view - Peter C Samuels (Journal of Learning Development in Higher Education)
Professional identity is an important concept within academia. However, in the complex, blurred environment of modern universities, it is becoming increasingly difficult to define. The concept of third space professionals may be seen as useful for theorising the practice of those who at least partly identify as learning developers. Having previously written in the journal about promoting learning development as an academic discipline, the purpose of this opinion piece is to reflect on how my personal experiences have reshaped my views since this article was published. This article draws on my personal professional journey from an academic researcher to a learning developer, to a faculty-based senior lecturer in a different discipline to my academic qualifications. I make eight claims relating to my experience, especially as an unofficial embedded learning developer. I then conclude that, firstly, third space professionals is a more useful concept for explaining the professional identity of unofficial learning developers; secondly, that learning development cannot yet be considered a fully-fledged academic discipline because there is no specific qualification or career path relating to its practice; and thirdly, that universities are still struggling to decide where best to position learning developers.